FINANCIAL CONTROL OF GOVERNMENT PROCUREMENT - A. Sokolova; O. Chokhatarova (Вестник Северо-Кавказского федерального университета, 2022)
The article deals with the peculiarities of state financial control in the public procurement system of Russia. In connection with the changes observed in the public procurement system, the issue of their state financial control is important. Financial control ofpublic procurement is an instrument of General financial control, as it is aimed at compliance with the law and improving the efficiency of budget expenditures. In addition, the article identifies problems in the field ofpublic procurement financing and presents measures to solve them. As a result, the necessity of using financial control ofpublic procurement is proved.